THE EXTENDED LONGEVITY OF A SMALL CORAL REEF SERRANID; A LESSON FROM CEPHALOPHOLIS CYANOSTIGMA (BLUE SPOT ROCK COD) OF THE CENTRAL GREAT BARRIER REEF, AUSTRALIA - Mosse, Jacobus W.; Davies, Campbell R. (Marine Research in Indonesia, 2007)
The blue spot rock cod, Cephalopholis cyanostigma, is a small common coral reef serranid that forms a significant proportion of the discarded by-catch in the Great Barrier line fishery. Samples were obtained by spear and line fishing at Orpheus Island (range 114- 294 mm FL, mean = 226 mm, n = 137) and from Pelorus Island (range 120-285 mm FL, mean = 214 mm, n = 125). Sagittal otoliths were used to obtain age-based parameter estimates for the populations at each island. Analysis of marginal increments on monthly samples suggested that a single opaque band was deposited annually during November - December. Recaptures of three fishes (9,18, and 24 years old) in July and November 1997, five years after injection of oxytetracycline, further corroborated our conclusion that band formation was annual. The maximum age in our samples of 31 years suggested that the blue spotted rock cod was one of the longest lived serranids documented to date. The von Bertalanffy growth function provided the best description of the pattern of growth for populations at both islands with high coefficients of determination (R2 = 0.86 and 0.82 for Orpheus and Pelorus islands, respectively). Female population of both sites grew relatively slow, not reaching asymptotic size until 7-10 yrs. Statistical comparisons on male and female growth patterns were not significant, however. There were significant differences in growth parameters between islands with C. cyanostigma on average growing larger at Orpheus Island (L?= 258 mm and K= 0.22) compared with Pelorus Island (L?=244 mm and K = 0.25). These age-based population parameter estimates indicated that C. cyanostigma was considerably longer lived than expected for a small coral reef serranid and further demonstrated the utility of age-based methods in studies of the demography of tropical reef fish. The implication for conservation and fisheries management of small tropical serranids is that species with similar population parameters are likely to sustain much lower levels of fishing mortality than previously thought.